Lessons from Reforming Financial Management Information Systems : A Review of the Evidence - Hashim, Ali (World Bank, Washington, DC, 2018)
Financial management information systems are a sine qua non in public financial management and play a foundational role in the execution of the budget. Recognizing their potential contribution to fiscal discipline, the strategic allocation of resources, and operational efficiency, significant time and resources have been invested by the World Bank and other development institutions into such systems across the world. However, the reform of financial management information systems tends to be complex, and the evidence base of causal effects and mechanisms is thin. This study develops a framework that outlines the various steps involved in reform that illustrate how change is expected to happen. Three major dimensions were identified: (1) diagnostic phase, (2) systems development lifecycle, and (3) coverage and utilization. The paper argues that reaching the financial management information systems production frontier requires optimization across these dimensions, and that a programmatically coherent approach is required to realize fully the expected improvements in budget management. The study identifies a set of lessons on the various stages that are mapped against the framework by triangulating findings from a systematic review of the financial management information systems literature, field-based project-level evaluations and protocol based case studies, and a comprehensive desk review of the World Bank financial management information systems project documentation.